Coping with oil spills: oil exposure and anxiety among residents of Gulf Coast states after the Deepwater Horizon Oil Spill. Issue 4 (27th May 2022) - Goldman, Zachary E.; Kaufman, John A.; Sharpe, J. Danielle; Wolkin, Amy F.; Gribble, Matthew O.
Abstract : In April 2010, a fatal explosion on the Deepwater Horizon drilling rig in the Gulf of Mexico resulted in the largest marine oil spill in history. This research describes the association of oil exposure with anxiety after the Deepwater Horizon Oil Spill and evaluates effect modification by self-mastery, emotional support and cleanup participation. To assess the impacts of the Deepwater Horizon Oil Spill, the Centers for Disease Control and Prevention (CDC) conducted the Gulf States Population Survey (GSPS), a random-digit-dial telephone cross-sectional survey completed between December 2010 and December 2011 with 38, 361 responses in four different Gulf Coast states: Louisiana, Florida, Alabama and Mississippi. Anxiety severity was measured using the Generalised Anxiety Disorder (GAD) symptom inventory. We used Tobit regression to model underlying anxiety as a function of oil exposure and hypothesised effect modifiers, adjusting for socio-demographics. Latent anxiety was higher among those with direct contact with oil than among those who did not have direct contact with oil in confounder-adjusted models [β = 2.84, 95% confidence interval (CI): 0.78, 4.91]. Among individuals with direct contact with oil, there was no significant interaction between participating in cleanup activities and emotional support for anxiety ( p = 0.20). However, among those with direct contact with oil, in confounder-adjusted models, participation in oil spill cleanup activities was associated with lower latent anxiety (β = −3.55, 95% CI: −6.15, −0.95). Oil contact was associated with greater anxiety, but this association appeared to be mitigated by cleanup participation.